MOT Collection : Rewinding the Collection 2nd. - Mizuta, Yuko (Tokyo : Museum of Contemporary Art Tokyo, 2022)
Kudo, Tetsumi ; Fujikawa, Eiko ; Asakura, Setsu ; Tabe, Mitsuko ; Lichtenstein, Roy ; Kitazawa, Eigetsu ; Hirata, Minoru ; Takamatsu, Jiro ; Anzai, Shigeo ; Rinke, Klaus ; Christo ; Andre, Carl ; Penone, Giuseppe ; Serra, Richard ; Narita, Katsuhiko ; Ueda, Kaoru ; Umehara, Ryuzaburo ; Suga, Kishio ; Nash, David ; Sugimoto, Hiroshi ; Kenmochi, Kazuo ; Kasahara, Emiko
MOT Collection: Rewinding the Collection 2nd, Museum of Contemporary Art Tokyo, Collection Gallery, 3 November 2022 - 19 February 2023
boek